An empirical analysis of Saudi Arabian women’s intentions to adopt hydrogen fuel cell cars - Yasmeen Ansari; Rohit Bansal; Sanjay Kumar Kar (Transportation Research Interdisciplinary Perspectives, 2024)
To successfully execute demand-side tactics for alternative energy, such as hydrogen, it is essential to thoroughly comprehend the preferences and circumstances that stimulate client demand. Thus far, studies have been scarce on female customers’ opinions, intentions, and behaviour towards various products in the Kingdom of Saudi Arabia (KSA). However, no studies have been conducted thus far, specifically on hydrogen fuel cell vehicles (HFCVs). Our study examines the key elements influencing women’s inclination to embrace HFCVs in the KSA. This study utilized an online questionnaire to gather data from 227 prospective female clients, thus conducting empirical research. To ascertain women’s intentions towards hydrogen fuel cell automobiles, we employed a structural equation modelling technique utilizing Smart-PLS 4.1. The findings of our study demonstrate that the perceived advantages, perceived barriers, public opinion, and government initiatives significantly influence the desire of women in Saudi Arabia to use HFCVs. The study suggests that the government should gather all pertinent stakeholders, including vehicle manufacturers, hydrogen producers, research institutes, and organizations, to address the challenges and accelerate the advancement of the hydrogen transportation system.